Resisting Patriarchy through Pop Culture: Stereotypes of Korean Women in a Global Perspective - Safira, Btari Anya (Devotion : Journal of Research and Community Service, 2024)
Korean dramas have made significant strides in gender representation in the past decade. However, South Korea continues to grapple with the deeply ingrained roots of misogyny and patriarchy. The study aims to explore how Korean women challenge stereotypes through pop culture of Korean women in a global perspective. The research employs a qualitative approach following Lawrence W. Neuman's framework, aiming to explore the underlying mechanisms and reasons behind the phenomenon. Through this approach, the research seeks to provide a nuanced understanding of how Korea's dramas contribute to the evolving discourse on gender roles in the globalized world. Specifically, the study examines how South Korean women confront stereotypes, particularly through the medium of Korean drama. The results of this study reveal that, despite the complexities within these narratives, Korean women continue to struggle with the challenge of capturing the full spectrum of female realities. In addition, the analysis reveals that women's experiences in Korean drama are shaped by a combination of relatable themes and an engaged audience, paving the way for Korean drama to act as powerful agents of social change, subtly dismantling long-held stereotypes via captivating storytelling.